(untitled) (Baghdad Science Journal, 2020)
In this study, the zinc oxide NPs have been synthesized from the fresh pomegranate peels extract using the precipitation method. The ZnO nanoparticles were produced from the reaction of fresh peels extract with zinc acetate salt which was used as zinc source in the presence of 2 M NaOH. The green synthesized nanoparticles were characterized through X-ray diffraction (XRD), UV-Vis diffuse reflection spectroscopy, Fourier transform infrared spectroscopy (FTIR), and Atomic force microscopy (AFM). The XRD patterns confirm the formation of hexagonal wurtzite phase structure for ZnO synthesized using pomegranate peels extract with average crystalline size of 28 nm. FTIR spectra identify the presence of many active functional groups for the pomegranate extract which is ideal to bind with zinc acetate to produce the ZnO nanoparticles during the preparation method. The reflection spectra of green synthesis ZnO with pomegranate extract observed a blue shift towards lower wavelength with (8 nm) difference compared to ZnO without the addition of any extract. The provenance of such blue shift towards shorter wave length was due to the quantum size effect. The Atomic force microscopic (AFM) result shows average roughness value for ZnO nanoparticles of 6.26 nm. The decolorization efficiency of the methylene blue dye was investigated using the ZnO nanoparticles under sun light irradiation and it was compared with the bare ZnO synthesized without the addition of extract. The catalytic activity was about 88% after 60 min of sunlight irradiation for both prepared catalyst however, the decolorization efficiency of ZnO with the addition of extract was higher at the first 16 min compared to bare ZnO.